The Greening of Economic Policy Reform:. Vol. 2 Vol. II: Case Studies. (Washington : World Bank Publications, 1997)
Annotation The economywide policy reform programs that have been undertaken in developing countries in recent years often address macroeconomic problems with little or no regard for their environmental impact, be it positive or negative. This book and its companion volume of case studies demonstrate that there are significant payoffs from a greater understanding of such impacts. The case studies, summarized in Volume I and presented in full in Volume II, provide empirical evidence of the links between macroeconomic policies and the environment and reflect a wide range of country situations and environmental problems: air pollution issues in Poland and Sri Lanka; deforestation and land degradation in Costa Rica; migration and deforestation in the Philippines; overgrazing of agricultural lands in Tunisia; overcultivation in Ghana; water resource depletion in Morocco; and wildlife management in Zimbabwe. The volumes also show the variety of analytical methods used to identify the linkages between policy actions and their environmental impacts. Also available: Volume I (ISBN 0-8213-3477-8) Stock no. 13477. Of related interest: "Environmental Impacts of Macroeconomic and Sectoral Policies" (ISBN 0-8213-3225-2) Stock no. 13225.
Annotation The economywide policy reform programs that have been undertaken in developing countries in recent years often address macroeconomic problems with little or no regard for their environmental impact, be it positive or negative. This book and its companion volume of case studies demonstrate that there are significant payoffs from a greater understanding of such impacts.The case studies, summarized in Volume I and presented in full in Volume II, provide empirical evidence of the links between macroeconomic policies and the environment and reflect a wide range of country situations and environmental problems: air pollution issues in Poland and Sri Lanka; deforestation and land degradation in Costa Rica; migration and deforestation in the Philippines; overgrazing of agricultural lands in Tunisia; overcultivation in Ghana; water resource depletion in Morocco; and wildlife management in Zimbabwe. The volumes also show the variety of analytical methods used to identify the linkages between policy actions and their environmental impacts.Also available: Volume I (ISBN 0-8213-3477-8) Stock no. 13477.Of related interest: Environmental Impacts of Macroeconomic and Sectoral Policies (ISBN 0-8213-3225-2) Stock no. 13225.
Scholarly & Professional World Bank Publications.
Keywords: Economic policy; Environmental economics